Meta-Analysis the Effect of Use Discovery Learning Models In Physics Learning Senior High School On Student Learning Outcomes - Sofia Rahmi; Festiyed Festiyed (PILLAR OF PHYSICS EDUCATION, 2022)
The 21st century is characterized by rapid advances in science and technology. These advances have an impact on education. In education, there is a curriculum that requires students to have good learning skills and results. The real conditions found in the field are low student’ learning results, the learning model is only used at one grade level and one unit of material. One model that can use to solve this problem is the discovery learning model. Research with the discovery learning model has been widely done and has not been summarized as a whole. Therefore, this research aims to determine the effect size of the discovery learning models through meta-analysis research reviewed based on aspects of knowledge, grade level, and subject matter. Meta-analysis research is conducted by summarizing, reviewing, and analyzing research data from the results of previous research. The articles reviewed in this research totaled 22 articles. The results of this research obtained, that the discovery learning model is effectively used in physics learning against student learning outcomes in the aspect of learning within an effect size of 0.196. At the class level, the model of discovery learning is more effective in class XI than class X with an effect size of 0.949. While viewed from the learning material unit, the model of discovery learning is more effectively applied to fluid mechanics material with an effect size of 1,196. So can be concluded the discovery learning model is very supportive of students' learning outcomes in high school physics learning.